Biopsychosocial implications in traffic accident victims who course with acquired disability - Silva, Fabiulla Costa Da (2020)
Objective: to understand the biopsychosocial implications in victims of traffic accidents who had acquired disability. Method: This is a descriptive research with a qualitative approach, developed in a University Health Center in a reference city of the Sertão Productivo Territory of Bahia, Brazil, with twelve victims of traffic accidents who attended with acquired disabilities. The information was collected through a semi-structured interview, in the period between August and September 2018. For the analysis of the information, the content analysis technique was used. Results: In the physical aspect, the traffic accident generated the restriction of autonomy, physical limitation to carry out basic activities in daily life, deterioration of skills and loss of independence. In the psychological aspect, the accident caused mental suffering, represented by feelings of hopelessness, sadness, stress, anger, guilt and fear, intensified by economic instability. In addition, the accident had a great social impact, such as restrictions on work, study and leisure. Conclusion:the disability acquired by a traffic accident has important repercussions on the lives of the victims, both physically and psychosocially. The formation of support networks made up of family members and the health team is essential to provide the necessary support to people in this new condition of life.